2019
DOI: 10.1007/s11738-019-2885-y
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic influence of common buckwheat root residues on selected weed species

Abstract: This study was conducted to determine if common buckwheat (Fagopyrum esculentum Moench) root residues (BRR) in soil are effective in limiting the growth and metabolic responses of barnyard grass (Echinochloa crus-galli (L.) P. Beauv.), wind grass (Apera spica-venti L.), cleavers (Galium aparine L.), and tiny vetch (Vicia hirsuta L.). After removal of above ground parts, BRR of 14-day-old buckwheat plants remained in soil for an additional 7 days when the weeds were seeded. After 30 days of growth, biomass of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…This is an important finding confirming the fact that their direct role in allelopathy is minor or even negligible. Moreover, the enhanced content of phenolic compounds in the soil containing BPR was not accompanied by inhibition of barnyardgrass growth, as was the case in the BRR-amended soil (Szwed et al 2019b). The content of soil-bound phenolic compounds which was many times higher compared with their free counterparts may highlight other problems that need to be clarified: are these compounds important in allelopathy and are organisms living in the soil (plants, bacteria, fungi) able to desorb these compounds?…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This is an important finding confirming the fact that their direct role in allelopathy is minor or even negligible. Moreover, the enhanced content of phenolic compounds in the soil containing BPR was not accompanied by inhibition of barnyardgrass growth, as was the case in the BRR-amended soil (Szwed et al 2019b). The content of soil-bound phenolic compounds which was many times higher compared with their free counterparts may highlight other problems that need to be clarified: are these compounds important in allelopathy and are organisms living in the soil (plants, bacteria, fungi) able to desorb these compounds?…”
Section: Discussionmentioning
confidence: 75%
“…Phenolic compounds (phenolic acids, flavonoids) were analysed by HPLC-MS/MS for the concentration of their various derivatives (free, esters, and glycosides). The profile and content of phenolic compounds were determined according to the method described previously (Szwed et al 2019b). Briefly, the phenolic derivatives extracted were dissolved in 80% methanol and subjected to HPLC-MS/MS analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite being the subject of many studies there is no conclusive evidence of which compounds are responsible for the allelopathic suppression of weed growth, although it has been suggested that phenolic acids and flavonoids could be responsible [ 21 , 22 ]. Buckwheat roots exudate to the rhizosphere allelochemicals with inhibitory effect on weeds mainly palmitic and gallic acid [ 23 , 24 ]. The roots extracts of buckwheat contain allelopathic flavonoids mainly catechin, and isoquercitrin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%